Macromolecular symposia 226 : - Deffieux, A. (Wiley-VCH Verlag HmbH, 2005)
Papers related to key invited lectures given at the World Polymer Congress "Macro 2004", covering polycondensation, polyaddition, chain polymerization, catalytic polymerization, functionalization, as well as polymer preparation in dispersed and unconventional media.